David versus Goliath, Writer versus Publisher: Fair Use in Literary Works as Applied in Anvil Publishing v. Adam David - Bernardo, Maria Karla Rosita V. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
In 2015, Adam David input numerous sentences from different short stories in the anthology Fast Food Fiction Delivery into a Javascript-based code. With a click of a button, the hypertext machine would produce a seemingly new story from the random quotes, creating a new whole from severed parts, a narrative that would appear coherent despite its fragmented origins. He then published this on a blog, entitled Hi Ma'am Sir. He considered this his critique of the said short story collection, as for him, it was meant to demonstrate what he thinks is s flattening of aesthetics, politics, language, and form in contemporary short story writing in the Philippines. Anvil, the publisher of Fast Food Fiction Delivery, threatened to sue David for copyright infringement. This note is an attempt to elucidate the application of fair use in appropriation art in literary criticism, and how it affects the progress and cultivation of arts in the Philippines.
Keywords: Fair use (Copyright)